Multifunctional agriculture: Policies and implementation in China. Issue 11 (24th August 2020) - Song, Bingjie; Robinson, Guy M.
Abstract: Multifunctional agriculture (MFA) has been supported in the European Union (EU) for over two decades, primarily as part of rural development policy in which agriculture is encouraged to deliver a range of economic, social and environmental outcomes. MFA has also grown in some countries without significant policy support, notably in peri‐urban fringes in North America and Australasia. Further expansion of this phenomenon is now apparent in China under strong central government policy directives from the early 2000s. Drawing upon a decade of studies of MFA in China, this paper examines some of the responses to various related policy initiatives, including major programs, such as Grain for Green, which have encouraged farmers to generate environmental services. It also refers to the scope for individual farm households to take initiatives leading to MFA via adoption of multiple functions on smallholdings (e.g., rural tourism, food processing). Various interpretations of MFA are explored, with a focus on how central government policy directives have driven take‐up of various MFA‐related initiatives.